2004
DOI: 10.2337/diacare.27.1.110
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Diabetes Care of Underinsured Patients Enrolled in Project Dulce

Abstract: OBJECTIVE -To improve clinical diabetes care, patient knowledge, and treatment satisfaction and to reduce health-adverse culture-based beliefs in underserved and underinsured populations with diabetes. RESEARCH DESIGN AND METHODS-A total of 153 high-risk patients with diabetes recruited from six community clinic sites in San Diego County, California were enrolled in a nurse case management (NCM) and peer education/empowerment group. Baseline and 1-year levels of HbA 1c , lipid parameters, systolic and diastoli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
155
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(161 citation statements)
references
References 33 publications
4
155
2
Order By: Relevance
“…Our finding that measures of team care were not associated with better diabetes control contrasts with reports of improvements in blood glucose control attributed to intensive nurse-directed diabetes interventions in recent controlled trails (43)(44)(45). On the other hand, our findings are consistent with those of a health care system-wide randomized trial of team diabetes care (2) that showed an increase in the utilization of preventive services (and less use of emergency room and specialty care services) but no greater change in HbA 1c (A1C) level in team care patients compared with those receiving usual care.…”
Section: Rubin and Associatescontrasting
confidence: 56%
“…Our finding that measures of team care were not associated with better diabetes control contrasts with reports of improvements in blood glucose control attributed to intensive nurse-directed diabetes interventions in recent controlled trails (43)(44)(45). On the other hand, our findings are consistent with those of a health care system-wide randomized trial of team diabetes care (2) that showed an increase in the utilization of preventive services (and less use of emergency room and specialty care services) but no greater change in HbA 1c (A1C) level in team care patients compared with those receiving usual care.…”
Section: Rubin and Associatescontrasting
confidence: 56%
“…Several studies have reported patients receiving medical advice were more likely to follow the recommendations, independent of race, gender, and other social factors (Deakin, Cade, Williams, & Greenwood, 2006;Phili-Tsimikas et al, 2004;Tang et al, 2005;Tang, Funnell, Brown, & Kurlander, 2010). Therefore, we hypothesize that gender will not be a factor in level of following advice.…”
Section: Purpose and Hypothesesmentioning
confidence: 94%
“…For the current study, items were modified to address beliefs about diabetes onset (rather than cancer). A 10-item (true/false) measure, previously validated in English and Spanish in this population, assessed the participants' diabetes-specific cultural beliefs (e.g., urine is a cure for diabetes) [35]. Items were summed to reflect the number of (erroneous) beliefs endorsed out of 10.…”
Section: Methodsmentioning
confidence: 99%